Denarycotyle bajacaliforniensis (Monogenea: Monocotylidae) of Rhinoptera steindachneri (Rhinopteridae) from Puerto Viejo, Baja California Sur, México - Gómez del Prado-Rosas, María del Carmen (2024)
Rhinoptera steindachneri Evermann & Jenkins, 1891 is a myliobatid elasmobranch distributed in the Pacific Ocean, from Baja California, including the Gulf of California, to Peru and it has been subject of parasitological studies in several states of Mexico. In the present work, a new species of monogenenean monocotylid, obtained from the gills of R. steindachneri collected from Puerto Viejo, Baja California Sur (BCS), is described. Their morphological characteristics are very similar to those described for Denarycotyle gardneri Pulido-Flores, Monks and Violante-González, 2015; however, the new species is distinguished from it by the following characteristics: hooks of the posterior medial septa lack sclerosed accessory piece, in the anterior region there is a sucker-like muscular structure in the center of which the mouth is located, no lateral glands to the pharynx are observed, the ejaculatory bulb is different in shape (it is ovoid and in some specimens it looks like a muscular barrel with longitudinal muscle fibers),  the terminal region of the male reproductive system is surrounded by a glandular mass that occupies the entire intercecal space, and the wall of the ootype is muscular and glandular tissue is observed inside. Puerto Viejo constitutes a new record of the geographical range for the Denarycotyle species. A modification is proposed in the diagnosis of the genus introducing the characters “hamuli with or without accessory piece. With or without glands lateral to the pharynx.  Seminal vesicle and ejaculatory bulb with or without glandular tissue occupying the intercecal space. Ootype with or without glandular tissue inside”.